Підготовка майбутніх магістрів «Дошкільної освіти» в сучасному ЗВО шляхом здійснення науково-дослідної діяльності та створенням ефективних умов для практичного застосування інновацій - Біда Олена; Bida Olena; Чичук Антоніна; Chychuk Antonina; Csicsuk Antonina; Кучай Тетяна; Kuchai Tatiana; Kucsáj Tetjána (Видавництво «Код», 2025)
Резюме. Стрімкий розвиток людської цивілізації, глобалізаційні процеси в суспільстві, його інформатизації підвищують вимоги до професійної, зокрема методичної, компетентності фахівців, майбутніх педагогів у системі дошкільної освіти. Студенти магістратури спеціальності А2 «Дошкільна освіта» повинні опанувати науковий стиль критичного мислення, а також такі його властивості, як системність, цілісність, логічність, аналітичність; бути готовими до проєктно-інноваційної діяльності, до здійснення науково-дослідної діяльності та створення ефективних умов для практичного застосування інновацій, вибудовувати нові концепції, траєкторію професійного розвитку; організовувати й проводити на високому науково-методичному рівні наукові дослідження.

Abstract. The rapid development of human civilization, globalization processes in society, its informatization increase the requirements for professional, in particular methodological, competence of specialists, future teachers in the preschool education system. Students of the master’s degree in the specialty A2 «Preschool Education» must master the scientific style of critical thinking, as well as its properties such as systematicity, integrity, logic, and analyticity; be ready for project-innovative activities, for carrying out scientific and research activities and creating effective conditions for the practical application of innovations, build new concepts, a trajectory of professional development; organize and conduct scientific research at a high scientific and methodological level. The article highlights a number of properties inherent in the system of training masters to ensure the quality of the educational process in a preschool education institution. It is proven that one of the tasks of master’s training is the formation of methodological competence in future teachers, which is considered a component of professional competence. The positions necessary for the effective training of future masters of preschool education in a modern innovative higher education institution are listed. Requirements for the selection of the content of training masters in preschool education for innovative professional activity are formulated. The main ones in the preparation of future masters of preschool education in a modern higher education institution in order to ensure the quality of the educational process in a preschool education institution by carrying out scientific and research activities and creating effective conditions for the practical application of innovations are the principles of forming the readiness of masters to ensure the quality of the educational process in a preschool education institution, which are shown in the article. In order for education seekers to have the opportunity to conduct high-quality and effective research in the conditions of an educational institution, areas of scientific and research activity are distinguished depending on the content and nature of the conduct, which are presented in the article. It is emphasized that special attention in higher education institutions is paid to the study of the issue of researcher ethics, as well as the peculiarities of the phenomenon of academic integrity, which is fundamental in writing a high-quality and independent research. For effective professional activity, the future educator is facilitated by the formed research skills presented in the article.
Training of future masters of «Preschool Education» in a modern university through implementation of scientific and research activities and creation of effective conditions for the practical application of innovations
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015727 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-13
Keywords: підготовка майбутніх фахівців; магістри «Дошкільної освіти»; ЗВО; заклади дошкільної освіти; науково-дослідна діяльність; інновації